The Concept of NEO Theater Performances: Appreciation for Acting - Tatang Abdullah (Institut Seni Indonesia Yogyakarta, 2018)
This research investigates NEO Theatre (NT) by using historical approach. Ithas several significances; i.e. firstly, NT is one of modern theater groups thatinfluences modern theater development in Bandung; secondly, though it is stillrelatively new, the creativity of NT cannot be separated from the history ofFathul A. Husein’s creativity development as its director. By applying methodof history through several stages from heuristics, critics, interpretation, tohistoriography; NT’s creativity pattern can be constructed; it is in accordancewith the aim of this research, to achieve the historical illustration of NT’screativity pattern in realizing the prototype of theater performance entitledTritik Segaris Putih. Fathul A. Husein, as the NT leader, was one of the foundersof theater Actors Unlimited (AUL) established in mid 1990s. Having it ended,Fathul A. Husein, who acted more as a director, founded NT on 18 April 2012.Based on the works Fathul directed since his time in AUL, the creative processof NT shows similar creativity with the Studiklub Theater Bandung (STB). Animportant fact to support this statement is that as a modern theater observerand critic, Fathul had ever joined in some productions of STB during the timeof Suyatna Anirun (RIP) before he decided to join in the founding of AUL. Thus,it can be said that the model of STB theater creativity pattern is also reflectedon the creativity pattern of NT in each of its theater production.Keywords: theater history; theater production; NEO Theater